The Relationship between the World of Archetypal Images and the World of Nature from the View of Allāma Tabataba'i and Sheikh Ishraq - Javad Parsā'i; Ahamad Shahgoli (آموزه‌‌های فلسفه اسلامي)
The discussion of the relationship between the world of archetypal images and the world of nature is one of the important issues of Islamic philosophy. Sheikh Ishraq rejected the theory of the peripatetic (Aristotelians) about the materiality of imaginary forms and proposed the theory of the world of archetypal images to explain some other issues of his philosophy. Allāma Tabataba'i is also one of the contemporary philosophers who has expressed significant theories about the world of archetypal images and its relationship with the world of nature. In this article, first, the views of two philosophers about the worlds of existence and their arguments in proving the world of archetypal images are explained; then to analyze the relationship between world of archetypal images and the world of nature in subjects such as the theory of illusory and vision, images in the mirror and knowledge of the unseen (mystic, invisible) affairs in Sheikh Ishraq and subjects such as the longitudinal and ambiguity (analogical gradation) relationship of the worlds, the causality of the world of archetypal images to the world of nature, the existence of perfections of the world of nature in the world of archetypal images and explanation of veracious dreams and the quality of sensory perception according to Allāma Tabataba'i, and in the end, some issues are said about the common and distinct points of view of these two philosophers and the challenges of each view.